Development Of Test Instruments To Measure High Order Thinking Skill (Hots) Mathematics Of Students In MTs 2 State Of Medan City: Pengembangan Instrumen Tes Untuk Mengukur High Order Thinking Skill (HOTS) Matematis Siswa Mtsn 2 Kota Medan - Siagian, Qania Agustika; Sagala, Prihatin Ningsih (Universitas Wiralodra, 2021)
The test instrument given by the teacher to students has not required students to think at a high level in mathematics, the important thing is that students must be familiar with questions that require High Order Thinking Skill (HOTS) to compete with other countries which can be seen in the TIMSS and PISA scores. The purpose of this study was to determine the students' high-order mathematical thinking skills, as well as to determine the validity, reliability, difficulty level, and differentiating power of the High Order Thinking Skill (HOTS) oriented test instrument. This developmental research uses the ADDIE type.. There were 57 students who were used as subjects in this study. The results showed that 15 questions that were considered successful and valid were developed, this is the average score of the test instrument assessment by experts of 91% and the validity of each test item is declared